The Antimalarial Chloroquine Suppresses LPS-Induced NLRP3 Inflammasome Activation and Confers Protection against Murine Endotoxic Shock - Xiaoli Chen; Ning Wang; Yuanfeng Zhu; Yongling Lu; Xin Liu; Jiang Zheng (Mediators of Inflammation)
Activation of the NLRP3 inflammasome, which catalyzes maturation of proinflammatory cytokines like IL-1β and IL-18, is implicated and essentially involved in many kinds of inflammatory disorders. Chloroquine (CQ) is a traditional antimalarial drug and also possesses an anti-inflammatory property. In this study, we investigated whether CQ suppresses NLRP3 inflammasome activation and thereby confers protection against murine endotoxic shock. CQ attenuated NF-κB and MAPK activation and prohibited expression of IL-1β, IL-18, and Nlrp3 in LPS treated murine bone marrow-derived macrophages (BMDMs), demonstrating its inhibitory effect on the priming signal of NLRP3 activation. Then, CQ was shown to inhibit caspase-1 activation and ASC specks formation in BMDMs, which indicates that CQ also suppresses inflammasome assembly, the second signal for NLRP3 inflammasome activation. In a murine endotoxic shock model, CQ effectively improved survival and markedly reduced IL-1β and IL-18 production in serum, peritoneal fluid, and lung tissues. Moreover, CQ reduced protein levels of NLRP3 and caspases-1 p10 in lung homogenates of mice with endotoxic shock, which may possibly explain its anti-inflammatory activity and life protection efficacy in vivo. Overall, our results demonstrate a new role of CQ that facilitates negative regulation on NLRP3 inflammasome, which thereby confers protection against lethal endotoxic shock.